Biosensors and sensors for dopamine detection. Issue 1 (13th September 2020) - Liu, Xixia; Liu, Juewen
Abstract: Dopamine is a key catecholamine neurotransmitter and it has critical roles in the function of the human central nervous system. Abnormal release of dopamine is related to neurological diseases and depression. Therefore, it is necessary to monitor dopamine levels in vivo and in real time to understand its physiological roles. In this review, we discuss dopamine detection focusing on the molecular recognition methods including enzymes, antibodies, and aptamers, as well as new advances based on nanomaterials and molecularly imprinted polymers (MIPs). A large fraction of these sensors rely on electrochemical detection to fulfill the requirement of fast, in situ, and in vivo detection with a high spatial and temporal resolution. These methods need to overcome interferences from molecules with a similar redox potential. In addition, fluorescent and colorimetric sensors based on aptamers are also quite popular, and care needs to be taken to validate specific dopamine binding. Combining aptamers or MIPs with electrochemistry promises to achieve rapid detection and increased selectivity. In this article, we pay more attention to the molecular recognition mechanism and critically review the sensor designs. In the end, some future directions are discussed. Abstract : Enzymes, aptamers, antibodies, and molecularly imprinted polymers have been developed to detect dopamine using electrochemical and optical signaling methods to address the analytical needs of fast, selective, sensitive, and in situ analysis of dopamine. On this topic, potential artifacts for sensor design are also critically evaluated.